Fibroblast Growth Factors in Depression - Deng, Zheng; Deng, Sheng; Zhang, Mu-Rong; Tang, Mi-Mi (Frontiers in Pharmacology, 2019)
Major depressive disorder (MDD) is one of the most serious diseases and now becomes a major public health problem in the world. The pathogenesis of depression remains poorly understood. Fibroblast growth factors (FGFs) belong to a large family of growth factors that are involved in brain development during early periods as well as maintenance and repair throughout adulthood. In recent years, studies have found a correlation between the members of the FGF system and depression. These signaling molecules may be expected to be biomarkers for the diagnosis and prognosis of MDD, and may provide new drug targets for the treatment of depression. Here, we reviewed the correlation between some members of the FGF system and depression.